Access to Triptans for Acute Episodic Migraine: A Qualitative Study. (14th July 2015) - Khan, Sobia; Mascarenhas, Alekhya; Moore, Julia E.; Knowles, Sandra; Gomes, Tara
Abstract : Objective: Our study aims to examine factors related to access of triptans among multiple stakeholder groups. Background: Triptans are a cornerstone of pain management for the acute treatment of migraine, but actual utilization of triptans is lower than ideal. Initial and continued access to triptans may be an important clinical issue in the acute treatment of migraines, but factors affecting access at the patient, provider, and health‐care system levels have not been comprehensively explored. Methods: A qualitative study was conducted in Ontario, Canada, between August 2013 and January 2014. Three participant groups were recruited to the qualitative study: (1) migraineurs who have experience accessing triptans; (2) physicians, including primary care physicians (PCPs) and neurologists, who have prescribed triptans; and (3) pharmacists who have dispensed triptans. Qualitative data were collected through one‐on‐one, semi‐structured telephone interviews. The framework approach was used for data collection and analysis. Results: Data collected from 19 migraineurs, 6 physicians, and 8 pharmacists were included in the analysis. Study participants discussed various factors that facilitate or hinder access to triptans, which were synthesized into four themes that emerged at the patient, provider, and health‐care systems levels: (1) awareness; (2) apathy; (3) advocacy; and (4) affordability. Across all participant groups, awareness of available treatments and coverage policies for those treatments were potential factors relating to timely drug provision. Participants describe apathy in terms of patients' health‐seeking behaviors and physicians' lack of concern toward migraine, which were seen as factors that could delay diagnosis and provision of appropriate treatment. Patients engaging in self‐advocacy enhanced their ability to seek timely and appropriate provision of triptans at the patient level. At the health‐care provider level, pharmacists were identified by patients as advocates for receiving more effective treatments for their migraines; pharmacists also self‐identified with the advocate role. The affordability of triptans was a key concern impacting access at the systems level, but coverage limitations (eg, quantity limits) were also described to influence the appropriateness of prescribed migraine treatment. Conclusion: This study fills a gap in knowledge about access to triptans and how this may be impacted by patient, provider, and health‐care systems barriers. Overall, our study sheds light on the experiences of prescribing, dispensing, and accessing triptans for migraine treatment, and unveils important information that can impact how patients access these drugs.